Adaptações neuromusculares e funcionais em decorrência da isquemia cerebral e do não uso aprendido - Faturi, Fernanda Maria (Universidade Federal de São Carlos, 2018)
A high percentage (50% to 70%) of post-stroke patients have loss of upper limb function (MS). The hemiparesis that occurs after stroke generates a range of alterations such as atrophy and muscle weakness impairing the function and daily life activities of these individuals. These changes may be related to the central nervous system (CNS) and also to skeletal muscle. Factors such as learned non-use may also aid in both neural and musculoskeletal changes leading to a maladaptive cycle and exacerbating limb function. Although it is known about the neural adaptations, little is known about the musculoskeletal mainly in upper limbs. A large part of the studies evaluate lower limb and the heterogeneity of comorbidities found in these patients hinder the conclusions of the results. Thus, the thesis studies were performed in order to respond if there is a musculoskeletal alteration after the stroke and if through learned non-use we can generate a model of atrophy or worsen functional deficits and musculoskeletal atrophy. Objectives: Both studies aimed to evaluate the neuromuscular and functional alterations after stroke. Methods: In study 1 a systematic review was conducted with search in December 2017 using the Medline, PubMed, Scopus, Cinahl and Web of Science databases. We investigated studies that performed image analysis in order to evaluate musculoskeletal adaptations after stroke. In study 2, a model of ischemic injury induced by endothelin-1 was performed, as well as training of the reach of the less affected forelimb of rats. Functional performance tests and morphometric analysis of the muscles were performed. Results: For the systematic review we included 7 studies with a wide variety of distal muscles evaluated, which obtained a reduction in the cross-sectional area, density, fascicle length and increase of pennation angle and variables responsible by the amount of connective tissue on the paretic side compared to non-paretic. In study 2, endothelin-1 induced ischemia impaired the paretic upper limb performance during the reach task without musculoskeletal alteration. Training of the non-paretic upper limb accentuated the learning non-use and induced atrophy of the finger extensors in the paretic upper limb. Conclusion: study 1 showed studies with poor to fair quality of evidence showing musculoskeletal changes in a paretic limb after stroke, however, the paretic and non-paretic side comparisons may be inappropriate and error-inducing, so well-designed studies addressing this issue are necessary. In study 2, it was concluded that ischemic injury induced by endothelin-1 causes dysfunction of the forelimbs without muscular alteration and late recovery of function is associated with compensatory movements and without atrophy. Non-paretic upper limb training impairs the recovery of the paretic limb and causes selective atrophy of the paretic side.
Keywords: Acidente vascular cerebral; Isquemia cerebral; Reabilitação; Extremidade superior; Paresia; Não uso aprendido; Alteração musculoesquelética; Atrofia; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA